Efektivitas Jangka Panjang Model Pembelajaran Proyek Berbasis Etnoekologi (E-PjBL) terhadap Restorasi Kognitif dan Konsolidasi Perilaku Pro-Lingkungan Remaja - Vivin Elfitriyah; Kusumaningrat; Nurasyah Dewi Napitupulu; I Komang Werdhiana (Postgraduate, University of Mataram, 2026)
Global conservation challenges demand a shift in environmental management towards cultural values and ecological reciprocity. This study aims to examine the medium-term impact of the Ethnoecology Project-Based Learning (E-PjBL) model in restoring students' focused attention and pro-environmental behaviour sustainability within three months after the intervention. This study uses a Quasi-Experimental design with a pretest–posttest–follow-up control group design. The sample involved 80 tenth-grade high school students divided into an experimental group (E-PjBL) and a control group. The experimental group implemented a Traditional Ecological Knowledge (TEK) exploration project for 14 weeks, while the control group used conventional methods. The results of the Mixed ANOVA analysis showed a highly significant interaction between time and group on cognitive restoration (p < 0.001). The experimental group showed a dramatic increase in directed attention scores from 66.1 on the pre-test to 82.3 at the follow-up stage, with moderate effectiveness (N-Gain Score 0.48). In contrast, the control group only achieved an N-Gain of 0.09 (low). Furthermore, the pro-environmental behaviour of the experimental group proved to be continuously internalised, as seen from the continuous increase in scores from the post-test (78.0) to the follow-up (81.4). The integration of local wisdom in E-PjBL proved to be effective as a transformative instrument for building a lasting conservation character and restoring mental fatigue in adolescents.